2020
DOI: 10.4093/dmj.2019.0093
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Once-Daily Insulin Degludec/Insulin Aspart from Basal Insulin Improves Postprandial Glycemia in Patients with Type 2 Diabetes Mellitus: Randomized Controlled Trial

Abstract: Background: To explore the efficacy and safety of switching from once-daily basal insulin therapy to once-daily pre-meal injection insulin degludec/insulin aspart (IDegAsp) with respect to the glycemic control of participants with type 2 diabetes mellitus (T2DM). Methods: In this multicenter, open-label, prospective, randomized, parallel-group comparison trial, participants on basal insulin therapy were switched to IDegAsp (IDegAsp group; n=30) or continued basal insulin (Basal group; n=29). The primary endpoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 19 publications
0
20
0
1
Order By: Relevance
“…At the end of the 12 weeks, HbA1c level was significantly decreased (7.5% to 7.3%) only in the IDegAsp group. IDegAsp was more effective in controlling blood glucose after dinner and before bedtime without causing any increase in hypoglycemia (64).…”
Section: Switching From Other Regimens In Insulin-treated Patientsmentioning
confidence: 95%
See 1 more Smart Citation
“…At the end of the 12 weeks, HbA1c level was significantly decreased (7.5% to 7.3%) only in the IDegAsp group. IDegAsp was more effective in controlling blood glucose after dinner and before bedtime without causing any increase in hypoglycemia (64).…”
Section: Switching From Other Regimens In Insulin-treated Patientsmentioning
confidence: 95%
“…Recently, Cho et al evaluated 59 Japanese patients (aged 20-80 years) with T2D who were on basal insulin (insulin degludec or glargine) at least for 12 weeks before enrollment. A 12 week, multicenter, open-label, randomized, prospective, parallel-group comparison, treat to target study was conducted (64). Patients were randomly assigned to continue basal insulin (n = 29) or to switch to IDegAsp (n = 30).…”
Section: Switching From Other Regimens In Insulin-treated Patientsmentioning
confidence: 99%
“…In the IDegAsp group, in a similar way to the IGlarU300 group, both FPG and HbA1c levels decreased significantly both in all patients and in the patients that were followed up until month 12 ( P < .001 for all). IDegAsp has been reported to be more effective than basal insulin in the regulation of PPG 16 . However, Ozcelik et al found no significant change in FPG and HbA1c levels after switching from intensive insulin to IDegAsp 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, IGlarLixi follows a once-daily subcutaneous injection regimen [15], while IDegAsp might require a twice-daily administration for optimal glycaemic control [21,22], though a recent study suggested higher efficacy of a once-daily injection of IDegAsp compared to basal insulin [23]. The advantage of once-daily injection cannot be underestimated given the prevalence of fear of injection and social discomfort among patients with diabetes on injectable therapy [24,25].…”
Section: Discussionmentioning
confidence: 99%